Hello hygiene? A campaign on smartphone hygiene - Aisha Lin Tamrend (2016)
This paper presents “Hello, Hygiene?”, a public health campaign by four final-year undergraduates from the Wee Kim Wee School of Communication and Information, Nanyang Technological University. Smartphone hygiene is a newly-identified construct of personal hygiene, emphasising on cleanliness of personal mobile devices to achieve better overall health and well-being. This paper introduces the concept of smartphone cleanliness, and addresses the pertinent lack of awareness that smartphones surfaces can carry harmful bacteria and germs.